PENGARUH MANAJEMEN SEKOLAH, PENGELOLAAN PEMBELAJARAN, DAN PERANAN KOMITE SEKOLAH TERHADAP PRESTASI PENDIDIKAN DI SDN RINTISAN MBS (Studi kasus di SDN 139, SDN 137, dan SDN 128 Palembang) - A Alinadia; Neni Amani (JURNAL KOMPETITIF, 2016)
This research aims to determine the effect of the School of Management , Learning Management, and the Role of the School Committee Against SDN Pioneering Achievement in Education MBS ( 139 Case Studies in SDN , SDN 137 , and 128 Palembang SDN ) .The hypothesis proposed ( 1 ) . There was a significant effect of school management , learning management and school committee together on educational achievement in SDN stub MBS , ( 2 ) . There was a significant influence on the performance manejemen school education in SDN stub MBS , ( 3 ) . There was a significant influence on the management of learning in the educational achievement of SDN stub MBS , ( 4 ) . There was a significant influence on the role of school committees in educational achievement MBS SDN stub. Keywords : Achievement of Education , School of Management , Learning Management , and the Role of the School Committee